The Community Empowerment, Health Promotion Strategies on Implementation Integrated Management of Childhood Illnes (IMCI) Through Local Wisdom- Matandook - Pinto, Joaquim; Wahyuningsih, Sayekti; Puspitasari, Yenny; Ana Anggraini, Novita (Journal of Neonatal Surgery, 2025)
Background: Integrated Management of Childhood Illness (IMCI) is needed to prevent mortality rate under five years old in sub-Saharan African and South Asian countries with occurring 11 million annually, due from diarrhea, pneumonia, measles, malnutrition, and newborn care problems. Timor Leste is a country that experiences many sick toddlers. Cases of sick babies in the city of Madya Aileu from 2022-August 2024 are dominant, namely cough, not pneumonia, and diarrhea. Meanwhile, the number of deaths of toddlers in the Municipality of Liquiça from 2022 to August 2024 was 0.034. Objective: This study aims to Assess of community empowerment, health promotion strategies on implementation of Integrated Management of Childhood Illness (IMCI) through local wisdom of Matandook. Methods: The research method used is a quantitative method with an observational study. The research sample was 400 samples. The research was analyzed using SEM with SMART Partial Least Square. Results: The results of the study show that 1) The effect of Community Empowerment (X1) on Local Wisdom-MatanDook (Y) P-Value is 0.012, which is 12%. 2) The effect of Health Promotion Strategy (X2) on Local Wisdom MatanDook (Y) P-value is 0.049 or 49%. 3) The influence of Local Wisdom MatanDook (Y) on the Implementation of IMCI (Z) P-Value is 0.050, which is 50%. 4) The Effect of Community Empowerment (X1) on the Implementation of IMCI (Z) The P-value is 0.064, which is 64.00%. 5) The Effect of Health Promotion Strategy (X2) on the Implementation of IMCI (Z) P-value of 0.057 is 57%. 6) The Effect of Community Empowerment (X1) on MatanDook (Y) on Implementation of IMCI (Z) The P-value is 0.065, which is 65%. 7) The Effect of Health Promotion Strategy (X2) on Local Wisdom (Y) Implementation of IMCI (Z) P-Value of 0.063 which is 63%. Conclusion: The findings suggest that Empowerment Model in (IMCI) is effective in Reducing Morbidity and Mortality of Childhood in Aileu and Liquça Municipalities. This community-IMCI helps and supports families in providing good care for their childs.